Elijah in Dorset: William Freke and Enthusiasm in England and the Atlantic World at the Turn of the Eighteenth Century - Greig, Martin (Church history, 2018)
In 1709, William Freke, a pious, well-educated, and well-read English gentleman living in Dorset, declared to the world that he was the second coming of Elijah, sent to announce the arrival of the New Jerusalem and to proclaim the beginning of Christ's reign upon earth. There is no evidence to indicate that anyone at the time took him seriously, and given this absence of contemporary interest, it might be tempting to dismiss Freke as an isolated and insignificant crackpot. But this would be a misreading of his career. Research over the past couple of decades has decisively determined that the twenty years following 1690 were a period of intense religious speculation in England and the larger Atlantic world when expectations of the millennium were high. Far from being an isolated enthusiast crying in the wilderness, Freke was in fact a prophet who was connected in a variety of ways to a much larger network of religious enthusiasts in England and on the Continent that reveals much about the religious milieu of, and the millenarian interconnections that existed during, the last decade of the seventeenth and first decade of the eighteenth century.